PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS DIGITAL DALAM PENINGKATAN KOMPETENSI PEDAGOGIK GURU - Maya Nurfitriyanti; Yogi Wiratomo; Abdul Karim (Dharmas Education Journal (DE_Journal), 2026)
This study aims to analyze the development of digital-based learning tools in improving teachers' pedagogical competence. This research is a development research with the ADDIE approach. The stages carried out in this study are Analysis, Design, Development, Implementation and Evaluation. This study develops digital-based learning tools and measures teachers' pedagogical competence based on the implementation of the development of these learning tools. The initial stage carried out was problem analysis by conducting FGD interviews to determine the digital-based learning tools created by teachers and administering an initial questionnaire on teachers' pedagogical competence. This research was conducted at SDIT Nurul Huda, East Jakarta. The subjects of this study were 10 teachers who teach at SDIT Nurul Huda, East Jakarta. Based on the results of this study, the development of digital-based learning tools can improve teachers' pedagogical competence, this is seen from the results of the t-test of 2.99 > t-table of 0.183. This can also be seen from the increase in the average score of teachers' pedagogical competence at the beginning of the observation, which was 40.90 and the average score of teachers' pedagogical competence after implementation of 57.10.